Al-Syams and al-Insyirah as treatment to reduces academic procastination among students of UIN SUSKA - Afrizal Nur,; Vivik Shofiah,; Muhd Najib Abdul Kadir, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Procrastination can occur to everyone, and it has happened from the past until now. Academic procrastination is the behavior of procrastinating work or delaying the completion of academic obligations carried out by several students which has an impact on delaying graduation and completion of college so that it has an impact on the future of these students and decreases college accreditation. The aim of this study was to provide a practical solution to reduce academic procrastination for students of the Quran and Tafsir Study Program at UIN Suska Riau with the treatment of contemplating its meaning surah al-Syams and al-Insyirah. The type of this study was pre-experimental one group pre and posttest design, pretest was undertaken before being given treatment, the results of the treatment can be known more accurately, due to it can compare with the situation before and after being treated. and Al-Insyirah can reduce the academic procrastination of students of the Quran and Tafsir Study Program, Faculty of Ushuluddin UIN Sulthan Syarif Kasim Riau.